2016
DOI: 10.1016/j.gaitpost.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Motor-cognitive dual-task deficits in individuals with early-mid stage Huntington disease

Abstract: Background. Huntington's disease (HD) results in a range of cognitive and motor impairments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 30 publications
(39 reference statements)
5
47
0
Order By: Relevance
“…Our findings are related to prior gait studies in HD where performing a cognitive‐motor DT resulted in decreased stride length, cadence, and gait speed, with increased gait speed DTC . Our findings are also consistent with the elevated DTC for combined cognitive and balance tasks in individuals with other neurodegenerative diseases, including MS and PD …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings are related to prior gait studies in HD where performing a cognitive‐motor DT resulted in decreased stride length, cadence, and gait speed, with increased gait speed DTC . Our findings are also consistent with the elevated DTC for combined cognitive and balance tasks in individuals with other neurodegenerative diseases, including MS and PD …”
Section: Discussionsupporting
confidence: 89%
“…Previously, difficulties in DT gait performance were associated with increased falls in PD and HD . We hypothesize that DT balance assessments and knowledge of how cognition impacts balance will provide important information about fall risk in HD.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cognitive deficits are also prevalent, notably in the domains of executive function, visuospatial processing, processing speed, and short-term memory, which can further exacerbate motor impairments [9,10]. Cognitivemotor dual-task paradigms are a means to assess an individual's ability to divide their attention during concurrent tasks and have been shown to reveal motor deficits not seen under singletask in Parkinson's disease (PD) [11], HD [8,12], and multiple sclerosis (MS) [13]. Under DT, individuals with HD have exhibited a decrease in gait speed, cadence, and stride length [8,12] compared to healthy controls, characteristics which contribute to an increased fall risk in other movement disorders [11].…”
mentioning
confidence: 99%
“…Cognitivemotor dual-task paradigms are a means to assess an individual's ability to divide their attention during concurrent tasks and have been shown to reveal motor deficits not seen under singletask in Parkinson's disease (PD) [11], HD [8,12], and multiple sclerosis (MS) [13]. Under DT, individuals with HD have exhibited a decrease in gait speed, cadence, and stride length [8,12] compared to healthy controls, characteristics which contribute to an increased fall risk in other movement disorders [11]. Previously, we found that individuals with HD exhibited significant DT cognitive motor interference for postural stability when vision was removed, and base of support was narrowed [14].…”
mentioning
confidence: 99%